Hubungan Kinerja Perawat Dengan Kepuasan Pasien Di Rawat Inap Ruangan Diamond IHC - Ervina junila rosario soares; Frengki Apryanto; MN. Lisan Sediawan (STIKES Widyagama Husada, 2026)
Abstract The success and achievement of a hospital are determined by the knowledge, abilities, creativity, and motivation of its staff and employees. These aspects are essential in shaping the hospital’s image. One of the key determinants of a hospital’s reputation is the quality of nursing services provided to patients. This study aims to examine the relationship between nurse performance and patient satisfaction at Lavalette Hospital, Malang. The research method used in this study is quantitative. The design applied is cross-sectional with an exploratory approach. The variables analyzed were nurse performance (X) and patient satisfaction (Y). A total of 54 respondents were involved, selected through a sampling technique. Data collection was conducted using a questionnaire that had been validated and tested for reliability as a research instrument. The data were analyzed using univariate analysis and bivariate analysis with the Spearman correlation test. The study results revealed that most respondents had a favorable perception of nurse performance, with the majority rating it good and only a small proportion assessing it as sufficient. In terms of patient satisfaction, most patients expressed satisfaction with nursing care, although a few indicated it was only sufficient, and some considered it inadequate. The correlation test results showed a p-value of 0.000 < 0.05, indicating a significant relationship between nurse performance and patient satisfaction. The correlation coefficient obtained was 0.571, demonstrating a positive, unidirectional relationship with a moderate strength between the two variables. Keywords: Nurse performance, patient satisfaction, hospital